(untitled) (Revista de Crítica Literaria Latinoamericana, 2023)
When the writer is a true artist, when his entire practice breaks the limits of a supposed specificity of genres, his life and his work constitute a singular reality. From this perspective, Copi (Raúl Damonte Botana, 1939-1987), far from stagnating in language and resorting to record permanence and acceptance, far from complying with mandates (ethical or aesthetic) that would place him at the heart of the norm, he displaces writing to plastic art and plastic art to acting. But even better: he makes a unique and simultaneous experience of all this, always from the moment of its constitution, from the very moment of the work or production that these unique stories carry out, made to be acted, seen and told.